EFFECT OF DIETARY PROBIOTICS SUPPLEMENTATION WITH DIFFERENT NUTRIENT DENSITY ON GROWTH PERFORMANCE, NUTRIENT RETENTION AND DIGESTIVE ENZYME ACTIVITIES IN BROILERS - Tang Zhi-gang; M. Naeem; W. Chao; W. Tian; Zhou Yan-min (Journal of Animal and Plant Sciences, 2014)
This study was involving a 2×2 factorial arrangement (2 nutrient density diets with 2 levels of probiotics), to evaluate effect of probiotics on growth performance, nutrient retention and digestive enzyme activities of broilers.Three hundred and twenty one-day-old chickens were randomly divided into four groups with 10 replicate of 8 broilers each for a 42-d feeding trial.The dietary were formulated: a positive control diet (PC) and a negative control diet (NC) to contain 320 KJ metabolizable energy /kg diet and 0.85 percentage crude protein less than PC, which both were supplemented with0 or 100 mg/kg probiotics. Broilers fed NC diet tended to reduce body weight（BW and average daily gain (ADG) (P=0.063) in starter phase (1-21 d). Probiotics treatments improved 21-d BW, ADG (P<0.05) and feed/gain ratio (P=0.078) in starter phase. Probiotics improved the retention of CP (P<0.05) during 11-14 d, but reduced the activity of lipase in pancreas of broilers (P<0.01) at 21 d. It was concluded that low nutrient density tended to reduce BW and ADG of broilers in starter phase, but probiotics improved the starter phase of growth performance and retention of CP, reduced pancreatic lipase activity of broilers.
Keywords: probiotic; nutrient level; nutrient retention; digestive enzyme; broiler